Foliar and topdressing application of nitrogen to the common bean crop - Tailene Elisa Kotz-Gurgacz; Rogério Peres Soratto; Fernando Vieira Costa Guidorizzi (Pesquisa Agropecuária Brasileira, 2018)
Abstract: The objective of this work was to evaluate the effect of applying N sources to leaves and N rates to the soil on the growth, N uptake, and grain and crude protein yields of the common bean (Phaseolus vulgaris) crop. Three experiments - two irrigated and one rainfed - were conducted during the 2012/2013 agricultural season, in a randomized complete block design with four replicates. The treatments consisted of the application of: four N rates (0, 45, 90, and 180 kg ha-1) to the soil, as topdressing in the V4 stage; and five N sources/rates - i.e., control, without foliar N application; 2.5 kg ha-1 N as conventional urea (N-CU); 5.0 kg ha-1 N-CU; 2.5 kg ha-1 N as slow-release urea-formaldehyde (N-SR); and 5.0 kg ha-1 N-SR - to leaves, in the R5 stage. Soil N fertilization, using rates between 124 and 180 kg ha-1, increases shoot N content and uptake, number of pods per plant, grain yield, and protein content and yield. Regardless of the growing environment and N application to the soil, the foliar supply of N as slow-release urea-formaldehyde increases grain and protein yields, whereas the greatest rate of N as conventional urea also increases grain yield.